LEGAL STUDY ON THE FOUNDATION OF THE FLAT OWNERS AND RESIDENTS ASSOCIATION(PPPSRS) - R. Suharto; Yudhi Hendra Kristian (Fakultas Hukum, Universitas Diponegoro, 2017)
Practically, many developers did not facilitate the foundation of the flat owners and residents association (PPPSRS) as what has been regulated in Law No.20/2011 on Flats. Many owners or residents of flats do not really care on the responsibility of creating PPPRS based on article 74 number 1. The researcher wanted to know the lawful effects to the developer after the absence of PPPSRS and the lawful follow up should be done in the end.